Analysis of Calculation, Deduction, Recording, and Reporting Income Tax Article 22 for Procurement of Goods at the Minahasa Regency Trade Service - Malonda, Jacky Jonathan; Sondakh, Jullie J.; Wangkar, Anneke (Formosa Journal of Applied Sciences, 2024)
Taxes as the main source of state income are very important in the Indonesian economy. Income Income Tax Article 22 is the example of the reponsibilities that mandatory complied with by a business entity or government agency. The objective is to examine the procedures for calculating, deduction, recording and reporting Article 22 Income Tax in relation to goods procurement activities conducted by the Minahasa Regency Trade Service. In examining this research, descriptive qualitative methodologies were employed. The research results indicate that there are 2 out of 9 transactions from goods procurement activities that are subject to Income Tax Article 22 which still experience errors in the calculation, deduction and recording processes, so they are not adhere to the provisions in Minister of Finance Regulation Number 59/PMK.03/2022.